Gingivitis, dental caries and tooth loss: risk factors for cardiovascular diseases or indicators of elevated health risks - P. V. Ylo¨ stalo (Blackwell Synergy, 2006)
Objectives: The results of earlier studies connecting dental diseases to cardiovascular diseases are inconsistent. Our aim in this cross-sectional study was to investigate whether there are associations of dental diseases and diagnosed angina pectoris among the 1966 Northern Finland Birth Cohort. Materials and Methods: A postal questionnaire was sent to all cohort members in 1997–1998. The number of replies totalled 8690. Angina pectoris was determined by asking whether the respondent had been diagnosed with angina pectoris. Gingivitis, dental caries and tooth loss were determined on the basis of self-reported gingival bleeding, presence of dental caries and six or more missing teeth. Results: We found overall associations of gingivitis (odds ratio (OR) 1.52, confidence interval (CI) 1.04–2.22), dental caries (OR 1.50, CI 1.04–2.18) and tooth loss (OR 1.53, CI 0.69–3.42) with the presence of angina pectoris. The associations were modified by gender and socioeconomic status. In addition, gingivitis, dental caries and tooth loss were also associated with several cardiovascular risk factors. Conclusion: There were associations of self-reported gingivitis, dental caries and tooth loss with angina pectoris. However, the associations between dental diseases and cardiovascular risk factors suggest that the associations may be because of confounding.